Utilization of Rice Straw from Sungai Balang, Muar as an Alternative for Oyster Mushroom Production - Mohd Syahmi Yusof,; Shaiful Rizal Masrol,; Noorsaiful Amri Suloh,; Nor Indahna Main, (Progress in Engineering Application and Technology, 2024)
Rice straw, rich in cellulose and hemicellulose, is a possible alternative sawdust as a nutrient-rich substrate for oyster mushroom cultivation, giving a sustainable and cost-effective media for widespread mushroom production.. The objective of this research is to produce oyster mushroom media by using rice straw sawdust, to investigate the effect of different substrate compositions between rice straw and rubber wood sawdust, and to develop a packaging box for rice straw substrate mushroom planting kit. The grown media has been produced with 25%, 50%, and 75% sawdust composition between RW and RS. The substrate with 100% RW and 100% RS were produced as the control samples for comparison. All substrate conditions were produced with the addition of 10% bran and 1% agricultural lime. In the oyster mushroom cultivation, media bagging, sterilizing, spawning, incubation, and substrate harvesting were conducted. The study also observed in mycelium movement, spawn movement, pinhead formation, cap dimension, and yield. The results show that the addition of RS to the RW substrate has accelerated the first pinhead formation compared to 100% RW and 100% RS. The 25% RW + 75% RS mixture had the highest yield which is 270.00g. This optimum composition recorded an average of 3.8cm in stipe length, 8.53cm in cap diameter, and 5.77g in total number of fruiting bodies.  The RS 100% produced the low yield with an average of 174.75g and with a stipe length 3.09 cm. Consequently, it has been proven that the substrates combined with RS produced a greater quantity and superior quality of edible mushrooms. Hence, the substrate containing a combination of RW and RS exhibited significant potential as a viable alternative growth medium for cultivating oyster mushrooms. Utilizing rice straw sawdust in the mushroom business can result in enhanced mushroom yields and superior quality, offering potential benefits to both the mushroom and rice straw sectors.